MANUSKRIP “LONTAR” SEBAGAI SUMBER PENULISAN SEJARAH LOKAL ALTERNATIF DI BALI - I Wayan Putra Yasa (Universitas Negeri Malang, 2020)
TThis research is based on the scarcity of local history writing sources and the exclusion of the lontar manuscripts from history writing, especially in Bali. The purpose of this study was to elaborate the source of lontar in Bali, the process of writing history with lontar, and the value contained in the source of lontar manuscripts. The method used is a historical research method consisting of heuristics, criticism, interpretation, and historiography. The results showed that in Bali there is a Gedong Kirtya Museum manuscript storage center, with a collection of lontar totaling 1,750 titles, Dutch archives 8,490 pieces, and lontar translations 5,381 titles. Lontar translations are grouped again into seven, namely the Vedas, Religion, Wariga, Itihasa, Babad, Tantri, and Overlays (Weda, Agama, Wariga, Itihasa, Babad, Tantri, and Lelampahan). Writing lontar-based history begins with a heuristic consisting of identifying the lontar, reading the contents /translating the lontar, the two criticisms then the process of interpretation and finally historiography. The values contained in the lontar manuscripts are scientific, educational, ethical, cultural, political, nationalism values.